2017
DOI: 10.1136/bjophthalmol-2016-309994
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal ziv-aflibercept for the treatment of choroidal neovascularisation associated with conditions other than age-related macular degeneration

Abstract: IVZ improves CMT in patients with CNV associated with causes other than AMD, but improvements in BCVA are modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…This finding was quite similar to those from recent studies performed on ziv-aflibercept on a larger number of patients [ 32 , 33 ] that discussed the application of ziv-aflibercept in different retinal diseases and detected a reasonable safety profile for the drug comparable with those of other anti-VEGF agents. Moreover, Braimah et al [ 11 ] studied the efficacy of ziv-aflibercept on retinal diseases other than AMD, such as high myopia, macular telangiectasia, central serous chorioretinopathy, choroidal osteoma, choroiditis, Best’s disease and idiopathic macular degeneration, and reported a marked reduction in CMT and a moderate improvement in BCVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was quite similar to those from recent studies performed on ziv-aflibercept on a larger number of patients [ 32 , 33 ] that discussed the application of ziv-aflibercept in different retinal diseases and detected a reasonable safety profile for the drug comparable with those of other anti-VEGF agents. Moreover, Braimah et al [ 11 ] studied the efficacy of ziv-aflibercept on retinal diseases other than AMD, such as high myopia, macular telangiectasia, central serous chorioretinopathy, choroidal osteoma, choroiditis, Best’s disease and idiopathic macular degeneration, and reported a marked reduction in CMT and a moderate improvement in BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were divided into two age groups to detect the influence of age on visual prognosis: group 1 included 12 patients ≥40 years old, and group 2 included the remaining eight patients, who were < 40 years old. Sample size calculation was based on the mean (SD) of BCVA pre- and post-treatment with ziv-aflibercept (0.67 (0.45) and 0.58 (0.43), respectively, based on previous research) [ 11 ]. G*power version 3.0.10 was used to calculate the difference between 2 paired readings using a 2-tailed t test with an α error = 0.05, a power = 80.0% and an effect size =0.65.…”
Section: Methodsmentioning
confidence: 99%
“…Case series reporting the results of ranibizumab (7,8,10,16), ziv-aflibercept (17), and bevacizumab (18) treatment for CNV unrelated to AMD have observed a ≥15 letter visual acuity gain rate of 36-57.1%. A <15 letter vision loss rate of 90.5-100% has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A <15 letter vision loss rate of 90.5-100% has been reported. Many studies in this area have reported a significant reduction in the CMT with anti-VEGF treatment (8,10,17,18). In a significant fraction of these studies, the patients had previously received other treatments for CNV or had received concurrent treatments during the study, which could affect treatment results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation